1876 Pa. Laws 105, No. 77, § 4 - (:unkn) unknown (General Publisher, 1876)
No person shall, at any time, kill any wild duck or goose with any device or instrument known as a swivel or punt gun, or with any gun other than such guns as habitually are raised at arm’s length and fired from the shoulder or shall use any net, device, instrument, or gun other than such gun as aforesaid, with intent to capture or kill any such wild duck or goose, under a penalty of ten dollars.
--
Keywords: HUNTING REGULATION